Warehouse Operational Administration in the Context of Increasing the Effectiveness and Efficiency of the Audio Business Unit Warehouse of PT XYZ - Novianti, Annisa Dwi; Ridha, Mohammad (UI Scholars Hub, 2026)
ABSTRACT This study analyzes the critical role of warehouse operational administration as a determinant of effectiveness and efficiency within the supply chain, focusing on the Audio Business Unit of PT XYZ. It posits that robust administrative processes are fundamental to optimizing warehouse performance, which in turn supports broader business unit objectives. Using a qualitative case study approach, this research conducted an in-depth investigation from September 1st to October 31st, 2025, employing data triangulation through direct observation, semi-structured interviews, and documents analysis. The findings confirm that the established operational administration system significantly contributes to enhancing warehouse effectiveness measured through accuracy and order fulfillment and efficiency, reflected in resource and time utilization. However, the study also identifies specific procedural and systemic obstacles that constrain peak performance. This research concludes that targeted improvements to the administrative framework are essential for achieving higher levels of operational excellence, thereby directly supporting the strategic goals of the Audio Business Unit. The insights offer a validated model for linking administrative rigor to tangible gains in warehouse performance. Direct observation, documents analysis, and semi-structured interviews are the three main methods of data collection in this research. Direct observation directly observes behavior/events. Semi-structured interviews dig up information through semi-structured conversations. Documents analysis collect data from written or recorded sources. Keywords: Warehouse, Warehouse Administration, Warehouse Activities, Operational Administration, Operational Efficiency, Process Effectiveness, Business Unit Performance, Qualitative Case Study, Supply Chain Optimization, Audio Business Unit of PT XYZ